Analysis of Main Facilities Utilization in Lambada Fishery Port, Aceh Besar - Kurnia, Kurnia; Syahputra, Faisal; Hidayat, Rachmat; Rahayu, Rosi (Jurnal Perikanan Terpadu, 2024)
The purpose of this study was to determine the level of utilization of basic facilities at the Lambada Fishing Port, Aceh Besar. This study was located at the Lambada Fishing Port, Aceh Besar. The data taken in this study were secondary data, this data was taken directly at the Lambada Fishing Port management office, namely data on fishing gear, catches, fishing fleets and facilities at the port. While primary data was taken directly at the Lambada Fishing Port using questionnaires, observations and interviews. The interview method used was the purposive sampling method. Analysis of basic facilities at the Lambada Fishing Port was carried out by calculating the level of facility utilization. The results showed that the Lambada Fishing Port has an area of 1 Ha. The pier which is 400m long, the utilization rate only reached 70,75%. The area of the port pool is 3 Ha, but the utilization rate is only 3%. The depth of the port pool is also not optimal when viewed from the number of fishing boat fleets that have run aground when anchored at the Lambada Fishing Port. The strategy that can be suggested is to improve the facilities and infrastructure according to the needs and provisions to support good fisheries activities